Flexible torque control for wind turbines considering frequency response under wind speed crossing region - Wang, Yingwei; Guo, Yufeng; Du, Yilin; Xu, Weimao (Frontiers in Energy Research, 2023)
The operational range of a wind turbine is typically divided into two regions based on wind speed: below and above the rated wind speed. The turbine switches between these two regions depending on the prevailing wind speed, but during the transition, the generator may experience transient shocks in torque, which can negatively impact both the mechanical loads of the turbine and the reliability of the power system. This paper presents a flexible torque control method for wind turbines, specifically designed to handle the transition between wind speed regions when the turbine is participating in frequency regulation. The study begins by analyzing the anomalous generator torque caused by traditional torque control during frequency response scenarios. Next, the paper develops two methods - dynamic de-loading and flexible torque control - to address these issues. The developed method sets transition regions based on the state of the generator's speed, which helps to reduce the impact of transient changes in generator torque. Importantly, the addition of transition regions does not require additional feedback, making the controller easy to implement. This work then analyzes the response characteristics of the proposed method under different de-loading factors and wind speeds using model linearization. Simulation studies are used to verify the effectiveness of the proposed method. Overall, this study demonstrates the potential of flexible torque control methods for wind turbines, which can help to mitigate the negative impacts of torque shocks and improve the reliability and efficiency of wind power systems.